2013
DOI: 10.3748/wjg.v19.i41.7129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cirrhosis on surgical outcome after pancreaticoduodenectomy

Abstract: Patients with periampullary tumours and well-compensated chronic liver disease should be routinely considered for PD at high volume centres with available expertise to manage liver cirrhosis. PD is associated with an increased risk of postoperative morbidity in patients with liver cirrhosis; therefore, it is only recommended in patients with Child A cirrhosis without portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 41 publications
4
47
1
Order By: Relevance
“…Pancreatic surgery is performed only in select cirrhotic patients. Nevertheless, an increasing number of case series show good results in select patients 457…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic surgery is performed only in select cirrhotic patients. Nevertheless, an increasing number of case series show good results in select patients 457…”
Section: Discussionmentioning
confidence: 99%
“…The main difficulty was the presence of portal hypertension due to liver cirrhosis Child A. Previous studies indicated poorer outcomes in cirrhotic patients with portal hypertension 79. Transjugular intrahepatic portosystemic shunt before abdominal surgery does not improve postoperative evolution after abdominal surgery in cirrhotic patients 10…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that the Child–Pugh classification was a prognostic factor of mortality and morbidity, which have been reported as 4% and 79%, respectively, in Child class A, and 55% and 100% respectively, in Child class B . Those recent studies suggest that LC should not be considered as an absolute contraindication to PD, particularly in patients with Child–Pugh A cirrhosis . However, it remains uncertain whether or not the Child–Pugh classification is sufficient to assess the risk of PD, and currently, there are no other prognostic or predictive factors other than the Child–Pugh score.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreaticoduodenectomy (PD) alone is a high-risk surgery for malignant pancreatic and periampullary disease, including some benign lesions, with an operative mortality of 5%, and postoperative complication ranging from 30-60%, even without LC [197,199]. 2013 study: Overall colorectal surgery mortality was 8.7% (non-liver disease) vs. 13.3% (non-cirrhotics), and 24.1% (cirrhotics) [203].…”
Section: Gastricmentioning
confidence: 99%
“…Pancreatic 2013 study: Cirrhotics are at risk for higher amount of statistically significant intraoperative blood loss of over 500 ml (P=0.015) [197].…”
Section: Gastricmentioning
confidence: 99%